The Morphosyntactic Structure of the Words Having the Root Nyata in the Indonesian Language: A Corpus-Linguistic Approach - Elsa Elsa (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
One issue which is frequently discussed in linguistic study is the connection between the principle of morphology and syntax. Morphosyntax is a term used in linguistics studying the application of morphology and syntax on grammatical categories. In short, morphosyntax is the combination between morphological and syntactic studies. The writer correlates the relation between morphology and syntax by applying corpus-linguistics, the study of language data on a large scale. Corpus-linguistics is used as a method to identify each form of morphological process in the word having root nyata in wider context. The result of this research shows the relationship between morphosyntactic structure and lemmatization (the process of determining the lemma for a given lexeme). According to Kamus Besar Bahasa Indonesia, the word having root nyata is classified as verb and noun with nyata as the head word. In this study, the word having root nyata does not merely belong to both verb and noun. Furthermore, the research indicates that morphological process alters not only its parts of speech but also its head word in dictionary.Keywords: morphosyntax, corpus-linguistics, lemma, dictionary, Indonesian language